Analysis of Sportfishing Tourism Potential A Phenomenological Study in Jatigede Reservoir - Gilang Nurfaizal; Rizal Ahmad Fauzi; Adang Sudrajat (Tadulako Journal Sport Sciences And Physical Education, 2026)
This study aims to analyze the potential for fisheries tourism development in the Jatigede Reservoir, Sumedang Regency, using a qualitative descriptive research method with an analytical framework of Marketability, Sustainability, Participation, and Disaster Mitigation (MSP-DM). Jatigede has a unique submerged forest ecosystem, unlike other dams, which serves as a habitat for large predatory fish such as Hampala and Channa, creating specific technical challenges for the national sportfishing community. Data collection was conducted through participant observation, document review, and in-depth interviews with managers, fishing communities, local communities, and the Indonesian Fishermen's Association (APRI). The findings reveal a paradox between economic exploitation and conservation; where massive digital promotion has made Jatigede a "new giant" of national fisheries but also puts pressure on the sustainability dimension. Efforts to limit the number of rafts often conflict with the drive for economic profitability of local communities. The study concludes that Jatigede's enormous potential can only be optimized if there is synchronization between regulations on the number of fishing gear and safety standards based on integrated risk management. Community participation has successfully transformed the village's economic structure through the service sector, but disaster mitigation remains reactive rather than preventative. Furthermore, Jatigede's vast potential can only be maximized if regulations on fishing gear quantities and safety standards are synchronized based on integrated risk management.